2022
DOI: 10.3390/chemosensors10010019
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Synthesis of Large Stokes Shift 2,6-Sulphur-Disubstituted BODIPYs for Cell Imaging

Abstract: Five new disubstituted 2,6-thioaryl-BODIPY dyes were synthesized via selective aromatic electrophilic substitution from commercially available thiophenols. The analysis of the photophysical properties via absorption and emission spectroscopy showed unusually large Stokes shifts for BODIPY fluorophores (70–100 nm), which makes them suitable probes for bioimaging. Selected compounds were evaluated for labelling primary immune cells as well as different cancer cell lines using confocal fluorescence microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Grignard reaction with MeMgBr was also performed with 3a , which very efficiently produced the methyl-substituted BODIPY at the boron center ( 5a ) in 84% yield. Finally, N -chlorosuccinamide (NCS)-mediated thiolation was performed easily at C2 and C6 with 4-methyl benzothiol to furnish 5b in excellent yield (81%) . All of these reactions confirmed that the meso -morpholino BODIPYs can undergo various types of reactions to produce a library of functionalized BODIPYs with a variety of optoelectronic properties.…”
mentioning
confidence: 79%
“…Grignard reaction with MeMgBr was also performed with 3a , which very efficiently produced the methyl-substituted BODIPY at the boron center ( 5a ) in 84% yield. Finally, N -chlorosuccinamide (NCS)-mediated thiolation was performed easily at C2 and C6 with 4-methyl benzothiol to furnish 5b in excellent yield (81%) . All of these reactions confirmed that the meso -morpholino BODIPYs can undergo various types of reactions to produce a library of functionalized BODIPYs with a variety of optoelectronic properties.…”
mentioning
confidence: 79%
“…A BODIPY core structure in molecular rotors grants large molar extinction coefficients, photostability and chemical inertness [ 17 , 18 , 19 ]. Furthermore, BODIPY-based probes can be easily functionalized at the appropriate positions to tune their sensitivity to micro-environment viscosity, polarity or temperature; increase the emission wavelength or Stokes shift; or direct the molecules to specific cells or organelles [ 20 , 21 , 22 , 23 , 24 , 25 ]. Recently, we demonstrated that the functionalization of meso -phenyl BODIPY (BDP-H) ( Figure 1 ) with a heavy-electron withdrawing –NO 2 group results in a viscosity-sensor with an extremely wide viscosity-sensitivity range (0.5–50,000 cP) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%